KEEFEKTIFAN MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP PEMAHAMAN KONSEP PADA MATERI GETARAN, GELOMBANG DAN BUNYI DITINJAU DARI PENALARAN LOGIS PESERTA DIDIK - Maharusu, Maharusu; Muliddin, Muliddin; Hamid, Rimba (Halu Oleo University)
This study aims to determine the effectiveness of the problem based learning towards understanding the concept in the material of vibration, wave and sound viewed from students logical reasoning.The population of the research was the eighth grade students of SMP Ilmiah Kendari. The sample of the research was 43 students divided into two classes. Experimental class consisted of 22 students was treated with problem based learning and control class consisted of 21 students was treated with direct instruction. Data collection was done by giving the students test of logical reasoning and understanding the concept. Data was analyzed by using descriptive statistic and inferential through t-test. The result of research shows that: 1) there is a significant difference between the average value of N-gain for understanding the concept to the students who have high logical reasoning who learn through a problem based learning and direct instruction; 2)there is a significant difference between the average value of N-gain for understanding the concept to the students who have low logical reasoning who learn through a problem based learning and direct instruction; 3) there is a significant difference between the average value of N-gain for understanding the concept to the students who have a combination of high and low logical reasoning who learn through a problem based learning and direct instruction. Keywords : Problem Based Learning, Direct Instruction, Understanding the Concept, Logical Reasoning, Vibration, Wave and Sound